2019
DOI: 10.3390/su11041161
|View full text |Cite
|
Sign up to set email alerts
|

Do Corporate Carbon Policies Enhance Legitimacy? A Social Media Perspective

Abstract: Stakeholders are increasingly concerned about climate change and companies’ commitment to anticipate future carbon-related risks, and grant or withdraw support depending on their perceptions of firms’ carbon performance. The aim of this research is to analyse which carbon-related factors influence stakeholders with regards to the legitimacy-granting process. The sample in this study includes 146 firms from North America and Europe committed to carbon mitigation, whose legitimacy is measured via social media in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 114 publications
(169 reference statements)
1
12
1
Order By: Relevance
“…Analyzing H2, "Size" was statistically significant (β = 0.450; p < 0.01) and thus, those universities with a higher number of students enrolled were more willing to establish different communication and participation strategies in order to enhance public online engagement. Therefore, while Galán-Valdivieso et al [85] found a negative influence of size on more active stakeholder participation, the outcomes of this paper were in accordance with Haro et al [28], who showed evidence of the positive effect of this factor on greater online engagement. A possible explanation relies on their greater exposure to public scrutiny, which leads to more attention, and in turn, reactions to information published in their social media.…”
Section: Explanatory Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…Analyzing H2, "Size" was statistically significant (β = 0.450; p < 0.01) and thus, those universities with a higher number of students enrolled were more willing to establish different communication and participation strategies in order to enhance public online engagement. Therefore, while Galán-Valdivieso et al [85] found a negative influence of size on more active stakeholder participation, the outcomes of this paper were in accordance with Haro et al [28], who showed evidence of the positive effect of this factor on greater online engagement. A possible explanation relies on their greater exposure to public scrutiny, which leads to more attention, and in turn, reactions to information published in their social media.…”
Section: Explanatory Analysissupporting
confidence: 89%
“…As for financial information, the findings differed from those obtained by Galán-Valdivieso et al [85] and Dunne et al [119], indicating that profitability data do not create higher levels of stakeholder commitment. In general terms, these results are shared by similar studies [8,29], indicating that the increase in information disclosure of the organization fosters stakeholder engagement with the social media of the organization.…”
Section: Explanatory Analysiscontrasting
confidence: 75%
See 2 more Smart Citations
“…It should be noted that the qualitative analysis of interviews is complimentary to other methods that assess decision-making processes. For instance, to obtain a more representative distribution of stakeholders, data could be gathered using surveys (e.g., [53,54]), social media (e.g., [55]), or workshops (e.g., [54]). Complimentary methods used to assess decision-making procedures include Analytic Hierarchy Process [56] and participatory mapping [54].…”
Section: Methodsmentioning
confidence: 99%